Message Conveyor by Motion for Paralyze People Powered Using RF Energy Harvesting - Indra, Win Adiyansyah; Mohd Shariff, Muhamad Shafiq Adam (International Journal of Integrated Engineering, 2020)
This paper developed message conveyor for paralyze people is designed to help communicate because some of the paralyze people cannot talk. This project is introducing the latest and current technology update in the world, RF energy harvesting. RF energy harvesting is an option to powering the circuit by converting RF energy to DC power. RF energy is generated from the ambient environment transmitted by millions of radio transmitters and telecommunications media around the globe, such as wireless internet, mobile phones, base station, broadcasting station, Wi-Fi and a Radio Frequency transmitter. RF energy is a long-lasting replacement of power if the Radio Frequency signal is present in the surrounding area. Arduino Mega is used in this project as it is easier to program the coding and a low power sensor. The project serves the needs of the community as it can paralyses people to communicate and can enhance the reduction of electricity bills as the RF signal controls the motion sensor.